EXPERIMENTAL DAMPING IDENTIFICATION OF A CANTILEVERED BEAM - Gonçalves, João Bosco; Soares, Álvaro Manoel de Souza (Revista Ciências Exatas, 2011)
This work addresses the modeling and experimental damping of a cantilevered beam. Its objectives are to describe the design and the implementation of an experiment to study the dynamics and the experimental identification of the beam’s damping matrix. To do so an experimental setup was assembled composed by a cantilevered beam a impact hammer and a accelerometer. The dynamic modeling and an experimental modal analysis identification in the frequency domain was applied to obtain the vibrations modes of the beam and a procedure to the identification of the system damping matrix based on Genetic Algorithms method’s was used do complete the model. The results are quite good and show a good agreement between the real and experimental systems.